Immediate Effect in the Retina and Choroid after 650 nm Low-Level Red Light Therapy in Children - Yang, Weiming; Lin, Feng; Li, Meiyan; Wei, Ruoyan; Zhou, Jiaqi; Zhou, Xingtao (Ophthalmic research, 2023)
Abstract Introduction: The objective of this study was to investigate the changes in the retina and choroid of children after 650 nm low-level red light therapy (LLRLT). Methods: In this prospective study, 25 subjects in the Shanghai Eye and ENT Hospital of Fudan University were included from August 2021 to September 2021. One eye was randomly selected to receive LLRLT for 3 min. Swept-source optical coherence tomography (OCT) and OCT angiography were used to measure retinal fovea perfusion density (RFPD), retinal fovea thickness (RFT), choroidal fovea blood flow (CFBF), and choroidal fovea thickness (CFT) before LLRLT, 5 min and 1 h after LLRLT. Baseline characteristics between LLRLT and non-LLRLT eyes were compared. Changes in the retinal and choroidal parameters were analyzed by ANCOVA models. SAS software was used for data analysis. The difference was considered statistically significant if p < 0.05. Results: There was no difference in baseline characteristics between LLRLT eyes and non-LLRLT eyes. The RFPD in LLRLT eyes significantly increased 5 min after LLRLT, and the increment was 1.70 ± 0.83% (p = 0.0389). The RFPD significantly decreased from 5 min to 1 h after LLRLT with a mean of −2.62 ± 0.86% decrement (p = 0.0031). The RFPD levels returned to baseline at 1 h after LLRLT (p = 0.8646). However, compared with insignificant RFPD changes in non-LLRLT eyes, there was no significant difference in RFPD changes at any sampling point. No significant changes in RFT, CFBF, and CFT were found in LLRLT eyes at each sampling point. Conclusion: Although 3 min of LLRLT has no effect on the choroid, it may cause a short-term transient increase in RFPD. It will provide theoretical support for the role of LLRLT in myopia control.